Pengaruh Value Co-Creation dan Customer Engagement Terhadap Customer Loyalty Pelanggan Kopi Kenangan dengan Customer Satisfaction sebagai Variabel Mediasi - Fatmawati, Tika Rellyana Novia; Adriyanto, Andhy Tri; Octavia, Ayu Nurafni (Universitas Katolik Soegijapranata, Semarang, 2024)
In the era of globalization, business competition is becoming increasingly fierce, making this research relevant in identifying factors that can increase customer satisfaction and loyalty amid evolving market dynamics. This study aims to examine the influence of Value co-creation and Customer engagement on customer satisfaction and loyalty of Kopi Kenangan in the city of Semarang. This study used a sample of 96 respondents using a purposive sampling technique. The data analysis method uses Partial Least Square (PLS) Software. The results of the study revealed that value co-creation has an effect on customer loyalty. However, value co-creation does not significantly affect customer satisfaction. Next, this study found that Customer engagement has a significant relationship with customer satisfaction and loyalty. In addition, this study also examines the role of satisfaction mediation in the relationship between Value Co-Creation and Customer engagement to customer loyalty, This finding shows that satisfaction does not mediate the relationship between Value co-creation and Customer loyalty, but mediates the relationship between Customer engagement and customer loyalty. The first limitation of this study is that the number of Kopi Kenangan outlets in Semarang City is only 2 outlets. Second, value co-creation has no effect on customer satisfaction and customer satisfaction cannot mediate the relationship between value co-creation and customer loyalty. The first upcoming research agenda is to observe more Kopi Kenangan outlets in central Java. Second, adding mediation variables such as trust variables.